PENGARUH OPINI AUDIT, KUALITAS AUDIT DAN AUDIT TENURE TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Ivanda Ayu Lestary; Zaenal Wafa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aimed to assess the impact of audit opinion, audit quality, and audit tenure on the punctuality of financial report submissions by firms listed on the IDX from 2020 to 2023. The research used the promptness of financial report submission as the dependent variable, while audit opinion, audit quality, and audit tenure served as the independent factors. This study's research population comprises all health sector enterprises registered with the IDX from 2020 to 2023, using a purposive selection procedure resulting in a sample of 13 companies. This research employs descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing as data analysis methodologies. The study's findings reveal that the audit opinion and audit quality factors do not substantially affect the timeliness of financial report submission, however the audit tenure variable does. The audit opinion, audit quality, and audit tenure factors significantly influence the timeliness of financial report submissions.